Economics and Its Enemies Two Centuries of Anti-Economics - Coleman, William Oliver (Palgrave Macmillan UK, 2002)
Anti-economics is described as the opposition to the main stream of economic thought that has existed from the Eighteenth-century to the present day. This book tells the story of anti-economics in relations to Smith, Ricardo, Mill, Walras, Keynes and Hicks as well as current economic thinkers. William Coleman examines how anti-economics developed from the Enlightenment to the present day and analyzes its various guises. Right anti-economics, Left anti-economics, Nationalist and Historicist anti-economics and Irrationalist, Moralist, Aesthetic and Environmental anti-economics